Financial price fluctuations in a stock market model with many interacting agents - Ulrich Horst (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
We consider a financial market model with a large number of interacting agents. Investors are heterogeneous in their expectations about the future evolution of an asset price process. Their current expectation is based on the previous states of their neighbors and on a random signal about the of the market. We analyze the asymptotics of both aggregate behaviour and asset prices. We give sufficient conditions for the distribution of equilibrium prices to converge to a unique equilibrium, and provide a microeconomic foundation for the use of diffusion models in the analysis of financial price fluctuations.
urn:nbn:de:kobv:11-10049758
Keywords: 330; behavioral finance; diffusion models; interacting Markov chains; stochastic difference equations